Peak‐to‐average power ratio reduction of orthogonal frequency division multiplexing systems using modified tone reservation techniques. (12th March 2015) - Liang, Hsinying; Chu, Hung‐Chi; Lin, Chuan‐Bi
Summary: This paper proposed a modified tone reservation (TR) technique that can reduce the peak‐to‐average power ratio (PAPR) of the orthogonal frequency division multiplexing (OFDM) system and is able to correct errors to avoid channel interference. The TR technique is a widely used PAPR reduction technique, which divides subcarriers of the OFDM system into two sets to generate peak‐canceling signals and transmit modulated data. The subcarriers used to reduce the PAPR are called the peak reduction tone sets. The mechanism of peak‐canceling signal generation is a primary factor in determining the quality of the PAPR reduction performance of the TR technique. Currently, two signal generation mechanisms exist: TR‐gradient‐based and TR‐clipping‐based techniques. Although TR techniques can effectively reduce the high PAPR in the OFDM system, TR techniques lack the ability to correct errors. Therefore, this paper combined block coded modulation codes and TR techniques to provide the modified TR techniques with error correction abilities. From the simulation results, the modified TR techniques had a superior effect on PAPR reduction performance compared with the conventional TR technique. The modified TR technique also possessed the ability to correct errors during signal transmission. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This paper proposed a modified tone reservation (TR) technique that can reduce the peak‐to‐average power ratio (PAPR) of the orthogonal frequency division multiplexing (OFDM) system and is able to correct errors to avoid channel interference. This paper combined block coded modulation codes and TR techniques to provide the modified TR techniques with error correction abilities. From the simulation results, the modified TR techniques had a superior effect on PAPR reduction performance compared with the conventional TR technique.